Investigating The Connection Between X-Linked Dominant Hypophosphatemic Rickets Syndrome and Endodontic Periapical Lesions: A Case Report - Kiouah Abdelhak (Journal of Advanced Therapeutic Science, 2024)
Vitamin D deficiency is known to affect bone healing 1. In this case report, the potential link between vitamin D, calcium, and phosphorus deficiency and periapical lesions is explored, offering fresh insights into the complex relationship between systemic health and dental pathology. This pathology is caused by a mutation in the PHEX gene on chromosome X, which encodes a protein necessary for vitamin D synthesis and phosphate reabsorption, which are essential for the mineralization of bone and teeth 23. A 25-year-old man with rickets and vitamin D deficiency presented to our clinic with recurrent abscesses in multiple teeth. Radiographic imaging revealed periapical lesions on multiple teeth with advanced endo-perio lesions on teeth 26 and 16, and a negative cold test on all his teeth. Despite successful endodontic treatment, the patient’s compromised metabolic healing raised concerns about the prognosis. This case report highlights the intricate interplay between vitamin and mineral deficiencies and dental health, emphasizing the need for cautious management and long-term follow-up.
Keywords: vitamin D deficiency